Factors Associated with Loss to Follow-up during Treatment for Multidrug-Resistant Tuberculosis, the Philippines, 2012–2014 - Thelma E. Tupasi; Anna Marie Celina G. Garfin; Ekaterina V. Kurbatova; Joan M. Mangan; Ruth Orillaza-Chi; Leilani C. Naval; Glenn I. Balane; Ramon Basilio; Alexander Golubkov; Evelyn S. Joson; Woo-jin Lew; Vivian Lofranco; et al. (Emerging Infectious Diseases, 2016)
To identify factors associated with loss to follow-up during treatment for multidrug-resistant (MDR) tuberculosis (TB) in the Philippines, we conducted a case–control study of adult patients who began receiving treatment for rifampin-resistant TB during July 1–December 31, 2012. Among 91 case-patients (those lost to follow-up) and 182 control-patients (those who adhered to treatment), independent factors associated with loss to follow-up included patients’ higher self-rating of the severity of vomiting as an adverse drug reaction and alcohol abuse. Protective factors included receiving any type of assistance from the TB program, better TB knowledge, and higher levels of trust in and support from physicians and nurses. These results provide insights for designing interventions aimed at reducing patient loss to follow-up during treatment for MDR TB.